2016
DOI: 10.1149/2.0021611jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production with a Simple and Scalable Membraneless Electrolyzer

Abstract: Ion-conducting membranes are essential components in many electrochemical devices, but they often add substantial cost, limit performance, and are susceptible to degradation. This work investigates membraneless electrochemical flow cells for hydrogen production from water electrolysis that are based on angled mesh flow-through electrodes. These devices can be fabricated with as few as three parts (anode, cathode, and cell body), reflecting their simplicity and potential for low-cost manufacture. 3D printing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…In addition to standard cationexchange-membrane-based electrolyzers, membrane-free systems have seen significant advances due to their tolerance for impurities in water feedstock and potentially lower upfront capital costs. [92][93][94][95] Moreover, the development of anion-exchange membranes can enable implementation of alkaline polymerelectrolyte-membrane electrolyzers that use high-performing and earth-abundant Ni-based catalysts. 96,97 These membranes must exhibit long-term stability and avoid excessive gas crossover even at lower sunlight-driven rates.…”
Section: Pathways For Pv-electrolysismentioning
confidence: 99%
“…In addition to standard cationexchange-membrane-based electrolyzers, membrane-free systems have seen significant advances due to their tolerance for impurities in water feedstock and potentially lower upfront capital costs. [92][93][94][95] Moreover, the development of anion-exchange membranes can enable implementation of alkaline polymerelectrolyte-membrane electrolyzers that use high-performing and earth-abundant Ni-based catalysts. 96,97 These membranes must exhibit long-term stability and avoid excessive gas crossover even at lower sunlight-driven rates.…”
Section: Pathways For Pv-electrolysismentioning
confidence: 99%
“…12 Removing the solid membrane in these systems decreases the ohmic losses and provides flexibility in the selection of catalysts in addition to a simplified cell design. [13][14][15][16] Controlling two-phase flows by topography induced variations of the bubbles' surface energy is another way of eliminating the need for a functional membrane. 17 In this paper, we implement experimental and numerical tools to investigate the dynamics of bubbles flowing in microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
“…14 More recently, a type II design was demonstrated that was based on angled mesh flow-through electrodes separated by an insulating baffle that was part of the device body. 15 This modification enabled the use of an extremely simple device body that was 3D printed as a single, monolithic component, and was furthermore amenable to in situ imaging of the crossover phenomenon and non-uniform current densities with high-speed video analysis.…”
Section: And the Curves Inmentioning
confidence: 99%